Religious Guidance Program In Developing Students’ Moral Character At Tirtayasa Junior High School, Bandar Lampung - Asa Rispika Putri; Umi Hijriyah; Devi Sela Eka Selvia (Lembaga Riset dan Inovasi Almatani, 2026)
This study aims to describe the implementation of a religious guidance program in developing students’ noble character at SMP Tirtayasa Bandar Lampung. This research uses a qualitative approach with a descriptive type. The research subjects include the principal, Islamic Education teachers, and students, while the research object is the implementation of the religious guidance program at the school. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing. The results show that the religious guidance program is implemented through various activities such as prayers before and after learning, congregational prayers, Qur’an recitation, religious advice, and the commemoration of Islamic holidays. The guidance is carried out through habituation, role modeling, and direct practice with the active role of Islamic Education teachers. The program has a positive impact on students’ character development, reflected in increased awareness of worship, discipline, politeness, and responsibility, supported by the school’s commitment and the active role of teachers, while the obstacles include limited worship facilities and differences in students’ backgrounds.